Environmental impact assessment of the agro-services symbiosis in frontier territories: case study Mendoza (Argentina) - Bonilla Gámez, Natalia (2021)
In the next 10 years, cities will house 60% of the world’s population, where in agro-urban frontier territories problems associated with land use and water distribution arise due to demand, the latter mainly in semi-arid regions. Due to the increase in urbanization and loss of agricultural areas, a model of agro-urban growth that contemplates the lowest use of resources must be proposed. Therefore, the aim of this study is to determine the environmental impact of the use of resources in frontier territories of semi-arid regions with conventional linear urban growth and the one that integrates agro-urban planning with circular and symbiosis vision in water cycle. The study is focused on Luján de Cuyo in Mendoza, Argentina. Through a life cycle assessment, environmental performance was evaluated. In addition, an ecoefficiency analysis was performed in relation to climate change and water consumption and the cost of the surface uses, as well as an assessment according to the multifunctionality of surface use. The outcomes illustrate that the scenario that integrates agriculture to the gardens and roofs (2 green plus) has the least environmental impacts, due to the circular vision that uses grey water and collected rainwater from the city into integrated agriculture. Compared to the linear scenario, both circular scenarios show a substantial reduction in water consumption (38-42%) and marine eutrophication (27-34%) and curtail freshwater eutrophication impacts. Futhermore, household’s energy is the most critical flow in most impact categories. Scenario 2 (integrates agriculture in gardens) reaches maximum eco-efficiency for water consumption, while for climate change, none of the proposed scenarios for urban growth reaches eco-efficiency. Additionally, scenario 2 green plus has the lowest climate change impact in terms of the multifunctionality of surface use (1.82E+05 kg CO2eq/ha). This study shows that it is possible to achieve a more sustainable frontier in terms of water and food, through a vision of circularity and symbiosis, with maintenance and integration of agriculture with urban growth.